Analisis penerapan konsep sustainable university dalam mendukung SDGs (studi kasus: pada dua universitas) - Nina Mellyana (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
Currently, the Sustainable Development Goals (SDGs) are an important topic often discussed. Not a few people assume that the SDGs are only a form of responsibility of business actors whose business activities damage nature. An educational institution must also play an active role in supporting the SDGs by applying the concept of sustainable university. The University conducts various sustainability activities to participate in sustainable development. Therefore, the purpose of this study is to find out the purpose and contribution of sustainability activities carried out by the university in support of the SDGs. This research was conducted with descriptive research. Based on the research that has been done, these two universities have applied the concept of sustainable university. According to the results of the study, university X is superior because it has shown its support for all indicators of SDGs. While university Y does not support the SDGs 2 indicator. Both universities are expected to maintain and improve their sustainability performance.